The Generalized Averaging Method with Physics Applications - Alvaro H. Salas S. (Mathematics and Computer Science: Contemporary Developments Vol. 1, 2024)
In this work, we consider the problem of solving strongly nonlinear oscillators making use of a generalized averaging method. We illustrate the efficacy of this method for the generalized Van der Pol-Duffing oscillator. We show that the amplitude of the limit cycle may be obtained by solving a quintic.